The Benefit and The Content of Lactic Acid Bacteria “Lactobacillus casei Shirota Strain” in Yakult - Tri - Ujilestari; Dian Fajarwati Susilaningrum; Bernita Adelia Damayanti; Maulina Afni Saputri; Rizal Nur Alfian (Indonesian Journal of Biology Education, 2021)
The purpose of this article is to determine the content of lactic acid bacteria in a probiotic beverage (Yakult) with a starter fermentation of Lactobacillus casei Shirota strain and to find out its benefits for digestion. In this study, the library research method was used by obtaining data and materials from journals. The author tries to describe the content of lactic acid bacteria “L. casei Shirota strain” in Yakult and its benefits for the digestive system. The results showed that the levels of L. casei Shirota strain in fermented milk were 1.27-1.70% with an average of 1.42%. In the Indonesian National Standard 01-2891-2009, the lactic acid bacteria content of L. casei Shirota in fermented milk was 0.5-2.0%. L. casei Shirota can produce lactic acid and acetic acid, so that, it can decrease intestinal pH and prevent pathogens bacteria’s growth. Probiotic beverage from fermented milk using L. casei is beneficial for consumption for its ability in inhibiting the growth and development of pathogenic bacteria in the gastrointestinal tract, help the absorption of vitamins and antioxidants, eliminate toxic components contained in food, as well as producing several vitamins through the synthesis of digestive enzymes.